Negatively charged residues of the segment linking the enzyme and cytolysin moieties restrict the membrane-permeabilizing capacity of adenylate cyclase toxin - Masin, Jiri; Osickova, Adriana; Sukova, Anna; Fiser, Radovan; Halada, Petr; Bumba, Ladislav; Linhartova, Irena; Osicka, Radim; Sebo, Peter (Scientific reports, 2016)
The whooping cough agent, Bordetella pertussis, secretes an adenylate cyclase toxin-hemolysin (CyaA) that plays a crucial role in host respiratory tract colonization. CyaA targets CR3-expressing cells and disrupts their bactericidal functions by delivering into their cytosol an adenylate cyclase enzyme that converts intracellular ATP to cAMP. In parallel, the hydrophobic domain of CyaA forms cation-selective pores that permeabilize cell membrane. The invasive AC and pore-forming domains of CyaA are linked by a segment that is unique in the RTX cytolysin family. We used mass spectrometry and circular dichroism to show that the linker segment forms α-helical structures that penetrate into lipid bilayer. Replacement of the positively charged arginine residues, proposed to be involved in target membrane destabilization by the linker segment, reduced the capacity of the toxin to translocate the AC domain across cell membrane. Substitutions of negatively charged residues then revealed that two clusters of negative charges within the linker segment control the size and the propensity of CyaA pore formation, thereby restricting the cell-permeabilizing capacity of CyaA. The 'AC to Hly-linking segment' thus appears to account for the smaller size and modest cell-permeabilizing capacity of CyaA pores, as compared to typical RTX hemolysins.
Keywords: Whooping Cough; Lipid Bilayers; AMP cyklický; hemolyziny; Cyclic AMP; lipidové dvojvrstvy; Cell Membrane Permeability; permeabilita buněčné membrány; perforin; Bordetella pertussis; adenylátcyklasy; Perforin; lidé; Humans; Adenylyl Cyclases; adenylátcyklasový toxin; Hemolysin Proteins; pertuse; Adenylate Cyclase Toxin